EKSPLORASI MINAT BELAJAR BAHASA ARAB DAN IMPLIKASINYA TERHADAP MAHARAH KALAM DI PESANTREN - Anyes Lathifatul Insaniyah; Atiqotul Maula Alfarihah (Universitas Islam Negeri Mataram, 2025)
This research aims to deeply explore the interest in learning Arabic among santri and its implications for Arabic speaking skills at Pondok Pesantren Darussalam Blokagung. This research uses a qualitative approach, with data collected thru in-depth interviews with students, teachers, and the head of the pesantren, as well as participant observation in the dormitory environment and daily language activities. The research findings indicate that the interest in learning Arabic among students at Pondok Pesantren Darussalam Blokagung is influenced by internal factors, namely self-awareness of the importance of Arabic as a key to understanding the Quran, Hadith, and classical Islamic texts, as well as basic experience in speaking Arabic. External factors include interactive learning, inspiring teachers, and an environment that supports communication in Arabic. High interest in learning is characterized by the courage and fluency to communicate without fear of making mistakes, even with limited vocabulary, as well as the initiative to communicate in Arabic anytime and anywhere. Conversely, students with low interest tend to experience anxiety and passivity in speaking, as well as limitations in using vocabulary. High interest in learning Arabic among students has a direct and significant impact on improving their speaking skills. Students with high interest will proactively seek opportunities to speak, both inside and outside the dormitory, because courage and confidence are the main assets for students to speak Arabic fluently. However, the main obstacle is the unsupportive environment for students who do not live in Arabic language dormitories, resulting in a limited vocabulary for daily communication.